Babe : the gallant pig - King-Smith, Dick.; Rayner, Mary (New York : Houghton Mifflin Company, 1983)
A piglet destined for eventual butchering arrives at the farmyard, is adopted by an old sheep dog, & discovers a special secret to success.
Keywords: Pig stories -- Reading (Textbooks).